2022
DOI: 10.1088/1748-9326/ac7342
|View full text |Cite
|
Sign up to set email alerts
|

A compound event-oriented framework to tropical fire risk assessment in a changing climate

Abstract: Tropical fire activity closely follows the co-occurrence of multiple climate stressors. Yet, it remains challenging to quantify how changes in climate alter the likelihood of fire risks associated with compound events. Recent abrupt changes in fire regimes in iconic landscapes in Brazil (namely the Pantanal and Xingu) provide a key opportunity to evaluate how extremely dry and hot conditions, both together and individually, have influenced the probability of large fires. Here we quantify the relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…As described in this work, some studies have begun to build a better understanding of the physical mechanisms connecting the occurrence of persistent hot and dry conditions in Brazil. However, to the best of our knowledge, and with the exception of the recent works of Libonati et al 33 and Ribeiro et al, 181 there is a clear gap in the identification and quantification of the spatial pattern and temporal evolution of impacts associated with CDHW in the country. We are confident that obtaining a better understanding of the coupled phenomena of HWs and droughts in the country is crucial to enhance the adaptive capacity of different sectors, such as public health, civil defense, agriculture, tourism, and public policy management.…”
Section: Future Perspectives and Recommendationsmentioning
confidence: 92%
See 2 more Smart Citations
“…As described in this work, some studies have begun to build a better understanding of the physical mechanisms connecting the occurrence of persistent hot and dry conditions in Brazil. However, to the best of our knowledge, and with the exception of the recent works of Libonati et al 33 and Ribeiro et al, 181 there is a clear gap in the identification and quantification of the spatial pattern and temporal evolution of impacts associated with CDHW in the country. We are confident that obtaining a better understanding of the coupled phenomena of HWs and droughts in the country is crucial to enhance the adaptive capacity of different sectors, such as public health, civil defense, agriculture, tourism, and public policy management.…”
Section: Future Perspectives and Recommendationsmentioning
confidence: 92%
“…In fact, to the best of our knowledge, the only explicit joint assessment on the present‐day impact of CDHW events on vegetation fires was a recent study for the 2020 fire season in the Pantanal region 33 . In addition, future fire danger forced by dry and hot conditions under climate change scenarios was only recently evaluated for two Brazilian regions, namely the Xingu Basin and the Pantanal 181 . Here, we attempt to go a few steps further, summarizing the efforts developed by the academic research community to describe these fire–CDHW relationships over the Pantanal wetlands, the Amazonia rainforest, and the Cerrado savannas.…”
Section: Impacts Of Cdhw Events On the Environment And Society: Early...mentioning
confidence: 99%
See 1 more Smart Citation
“…Feng and Hao (2020) associated the yield loss across the United States and France in 61% of cases with compound dry and hot conditions in a global study across top maize-growing countries (Feng and Hao, 2020). In another global study, He et al (2022) reported that in each wheat-growing season, more than 92% of the global wheat-growing regions have faced at least one dry and hot CE during 1981-2020, along with increases of 28.2% and 33.2% in the CE frequency and duration, respectively. Furthermore, among the wheat-producing regions, Europe, eastern China, western United States, and northern Argentina have been identified as hotspots (He et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the association of droughts with other events, such as pluvial floods, was reported in 5.9%-7.6% of global land areas between 1950 and 2016, with pluvial floods following approximately 11% of droughts during boreal spring-summer or fall-winter (He and Sheffield, 2020). For event combinations of heatwave and ozone (O 3 ), Ban et al (2022) predicted an increase of 34.6 in annual mean CE days under high-emission scenarios (shared socioeconomic pathways (SSP): 3-7.0) in 2071-2090 compared with the historical baseline of 1995-2004 in a global analysis (Ban et al, 2022). Mukherjee and Mishra (2018) reported an increase of 2-12 times in the concurrent day and nighttime heatwaves using various representative concentration pathways (RCPs), namely, RCP 2.6-8.5 (Mukherjee and Mishra, 2018).…”
Section: Introductionmentioning
confidence: 99%